One-Pot Approach Towards Peptoids Synthesis Using 1,4-Dithiane-2,5-Diol via Multicomponent Approach and DFT-Based Computational Analysis - Musrat Shaheen; Akbar Ali (Molecules)
Peptoids are peptidomimetics in which the side chain is attached to the nitrogen of the amide group rather than the α-carbon. This alteration in the backbone structure is highly valued because it endows beneficial properties, including enhanced resistance to proteolysis, greater immunogenicity, improved biostability, and superior bioavailability. In this current study, we focused on the Ugi-4CR-based one-pot synthesis of peptoids using 1,4-dithiane-2,5-diol as the carbonyl component together with amine, carboxylic acid, and isocyanides. Four new peptoids—5a, 5b, 5c, and 5d—were designed and efficiently prepared in good chemical yields and were subjected to DFT investigations for their electronic behavior. These compounds have free OH, SH, and terminal triple bonds for further chemistry. In a computational analysis, the spectral data of compounds 5a–5d were juxtaposed with calculated spectral values derived from the B3LYP/6-311G(d,p) level. The electronic excitation and orbital contributions of 5a–5d were predicted using TD-DFT calculations. A natural bond order (NBO) analysis was utilized to investigate the electronic transition of newly synthesized peptoids, focusing on their charge distribution patterns. Furthermore, MEP and NPA analyses were conducted to predict charge distribution in these compounds. The reactivity and stability of the targeted peptoids were evaluated by global reactivity descriptors, which were determined with frontier molecular orbital analysis. The DFT results revealed that compound 5c displayed marginally higher reactivity compared to 5a, 5b, and 5d, possibly due to its extended conjugation.